Vasopressin After the Fontan Operation. (January 2016) - Kumar, T. K. Susheel; Kashyap, Pooja; Figueroa, Mayte; Zurakowski, David; Allen, Jerry; Ballweg, Jean A.; Sathanandam, Shyam; Ali, Mohammed; Knott-Craig, Christopher J.
Background: Prolonged pleural effusion following Fontan operation is common and increases morbidity and hospital length of stay. Vasopressin (VP), a neurohypophysial hormone, has numerous effects on the cardiovascular system. The most notable is increased peripheral vascular resistance, but it may also reduce capillary leakage by tightening endothelial intercellular junctions and reducing capillary hydrostatic pressure We reviewed our experience with the perioperative administration of VP following Fontan operation. Methods: We retrospectively reviewed the records of 62 consecutive patients who underwent Fontan operation from January 2004 to June 2014. In January 2010, VP was introduced as part of the standard perioperative management of patients undergoing Fontan operation at our center. For this retrospective observational study, patients were grouped according to the use (VP; N = 40) or nonuse (non-VP; N = 22) of VP (0.3-0.5 mU/kg/min) in the perioperative period. The primary end point analyzed was chest tube output. Secondary end points analyzed included fluid balance and length of hospital stay, with groups compared using Mann-Whitney U test. Results: There was no hospital mortality. Median total chest tube output was 22 mL/kg in the VP group and 68 mL/kg in the non-VP group ( P < .001). The median total duration of chest tube indwelling time was five days in the VP group and was 11 days in the non-VP group ( P < .001). Median fluid balance on first postoperative day was 13 and 38 mL/kg, respectively ( P < .001). Median hospital stay for VP and non-VP groups was 9 and 16 days, respectively ( P = .002). Conclusions: The more recent group of patients undergoing Fontan operations, all of whom received VP perioperatively, had less chest tube output and shorter duration of chest tube drainage after the Fontan operation relative to the earlier patient group whose perioperative management did not include VP. They also experienced less positive fluid balance in the early postoperative period and shorter hospital length of stay than the patients from the earlier era.